Functional genomics of corrinoid starvation in the organohalide-respiring bacterium Dehalobacter restrictus strain PER-K23 - Rupakula, Aamani; Lu, Yue; Kruse, Thomas; Boeren, Sjef; Holliger, Christof; Smidt, Hauke; Maillard, Julien (Frontiers in Microbiology, 2015)
De novo corrinoid biosynthesis represents one of the most complicated metabolic pathways in nature. Organohalide-respiring bacteria (OHRB) have developed different strategies to deal with their need of corrinoid, as it is an essential cofactor of reductive dehalogenases, the key enzymes in OHR metabolism. In contrast to Dehalococcoides mccartyi, the genome of Dehalobacter restrictus strain PER-K23 contains a complete set of corrinoid biosynthetic genes, of which cbiH appears to be truncated and therefore non-functional, possibly explaining the corrinoid auxotrophy of this obligate OHRB. Comparative genomics within Dehalobacter spp. revealed that one (operon-2) of the five distinct corrinoid biosynthesis associated operons present in the genome of D. restrictus appeared to be present only in that particular strain, which encodes multiple members of corrinoid transporters and salvaging enzymes. Operon-2 was highly up-regulated upon corrinoid starvation both at the transcriptional (346-fold) and proteomic level (46-fold on average), in line with the presence of an upstream cobalamin riboswitch. Together, these data highlight the importance of this operon in corrinoid homeostasis in D. restrictus and the augmented salvaging strategy this bacterium adopted to cope with the need for this essential cofactor.